Financial Analysis of Saudi Banks: Economic Perspective of NCB and BSF Analysis - Alamoudi, Abdulrhman (Archives of Business Research, 2024)
This study shows the importance of financial analysis in understanding a company's financial health, revealing its strengths, weaknesses, and potential opportunities. This article uses information from two publicly held banks in two consecutive years (2018-2019) of annual reports in Saudi Arabia. It aims to apply several financial tools, namely horizontal, vertical, and ratio analysis, to analyze NCB and BSF.